High-Resolution Mapping of Barley mild mosaic virus Resistance Gene rym15 - Wang, Yaping; Habekuß, Antje; Jayakodi, Murukarthick; Mascher, Martin; Snowdon, Rod J.; Stahl, Andreas; Fuß, Janina; Ordon, Frank; Perovic, Dragan (Frontiers in Plant Science, 2022)
Barley yellow mosaic virus (BaYMV) and Barley mild mosaic virus (BaMMV), which are transmitted by the soil-borne plasmodiophorid Polymyxa graminis, cause high yield losses in barley. In previous studies, the recessive BaMMV resistance gene rym15, derived from the Japanese landrace Chikurin Ibaraki 1, was mapped on chromosome 6HS of Hordeum vulgare. In this study, 423 F4 segmental recombinant inbred lines (RILs) were developed from crosses of Chikurin Ibaraki 1 with two BaMMV-susceptible cultivars, Igri (139 RILs) and Uschi (284 RILs). A set of 32 competitive allele-specific PCR (KASP) assays, designed using single nucleotide polymorphisms (SNPs) from the barley 50 K Illumina Infinium iSelect SNP chip, genotyping by sequencing (GBS) and whole-genome sequencing (WGS), was used as a backbone for construction of two high-resolution maps. Using this approach, the target locus was narrowed down to 0.161 cM and 0.036 cM in the Igri × Chikurin Ibaraki 1 (I × C) and Chikurin Ibaraki 1 × Uschi (C × U) populations, respectively. Corresponding physical intervals of 11.3 Mbp and 0.281 Mbp were calculated for I × C and C × U, respectively, according to the Morex v3 genome sequence. In the 0.281 Mbp target region, six high confidence (HC) and two low confidence (LC) genes were identified. Genome assemblies of BaMMV-susceptible cultivars Igri and Golden Promise from the barley pan-genome, and a HiFi assembly of Chikurin Ibaraki 1 together with re-sequencing data for the six HC and two LC genes in susceptible parental cultivar Uschi revealed functional SNPs between resistant and susceptible genotypes only in two of the HC genes. These SNPs are the most promising candidates for the development of functional markers and the two genes represent promising candidates for functional analysis.